The Effect of Visual Composition Created by Mosque Envelope in Generating Solemnity - Wisnu Hendrawan Bayuaji; Pramitasari, Dewi; Ratnasari, Zusnita (Departement of Architecture, Universitas Islam Indonesia, 2024)
The architecture of the mosque building is one of the most developed building typologies in Indonesia, and it has a high variation of form. This study evaluates how the mosque envelope affects its primary function as a prayer hall. Religious worship that requires solemnity is influenced by a spiritual atmosphere where lighting is important. This study takes a deeper step by identifying the lighting configuration produced by the openings in the mosque envelope and evaluating its effect on solemnity. Illumination data, building physical information of envelope and openings, and calibrated photo documentation are collected from three Yogyakarta Mosque building cases representing vernacular, Middle Eastern, and contemporary styles. These data are analyzed according to light intensity, contrast ratio, light distribution, and visual acuity to identify how it affects the formation of a spiritual atmosphere through the generation of visual performance, such as concentration and ability to focus, mood, and comfort. Bright, high-contrast, dramatic, and colored light can undermine the potential for evoking solemnity, while dim, low-contrast, uniform, and natural intensity prevents distractive visual information from flowing into the brain, resulting in a less challenging effort to focus and concentrate. A uniform light generates more visual comfort compared to high contrast as it maintains less eye-adaptation. A serene, calm, dim, humble, and soothing ambient is considered relevant to the generation of solemnity as it promotes humility and assists the prayer to feel calm and relaxed. Further research is needed to reveal the optimal model of mosque shape and opening configuration that contributes positively to the generation of solemnity. Keywords: Mosque envelope; solemnity; visual composition